The role of the tryptophan metabolites in gut microbiota-brain axis and potential treatments: a focus on ischemic stroke - Qin, Na; Xie, Xiaodi; Deng, Rong; Gao, Shiman; Zhu, Ting (Frontiers in Pharmacology, 2025)
Gut microbiota disturbances can elevate the risk of stroke by contributing to cerebrovascular events. Particularly, the gut tryptophan (TRP) metabolite is an essential mediator of the gut-brain axis. This review highlights the role of TRP metabolism in stroke, the influence of intestinal microbiomes on stroke pathology via TRP metabolism, and the gut-brain axis interactions. Recent studies indicate that various bioactive molecules produced via TRP metabolism can regulate various neurological functions and interrupt stroke pathophysiology. Moreover, the relationship between gut TRP metabolism and stroke development has been verified. TRP metabolism involves three pathways: kynurenine, 5-hydroxytryptamine, and indole, which potentially regulate post-stroke, may function as aryl hydrocarbon receptor agonists to modify neuronal excitotoxicity, and offer crucial targets for stroke treatment. This suggests that modulating TRP metabolite levels through various methods can enhance the prognosis of central nervous system diseases and restore microbiota-gut-brain axis functions.